(untitled) - Lovins, Amory B. (New York, 1980)
For those wishing to play a responsible role in shaping energy decisions now being made around the world. Amory Lovins provides a great store of vital information. World Energy Strategies avoids easy and canonically received answers, concentrating on a careful explanation of technical assessment regarding the nature and magnitutde of constraints upon our already inadequate energy resources. Within that context, lovins suggests where the merits may lie in technical disputes and shows not ony what energy options exist for the long term but also what short-term actions must be avoided if we are to preserve those options. "The main reason for Lovin's importance is that he has managed to redefine the energy problem, and thereby to change the frame of reference of a large number of technical debates. He has first-rate credentials as a nuclear physicist and, in his words, a former high technologist." He is familiarwith a staggering body of recent literature on energy. He writes clearly and often eloquently. All of these things help, but his appeal is that he has managed to define a pattern against which a jumble of technical choices can be compared and evaluated" - Fred D. Baldwin THE NATION
Keywords: Chính sách năng lượng,Energy policy